Spiritual Experience of Productive Age Hypertensive Patients Conducting Therapy Programs at Aisyiyah Hospital of Kudus - Sukarmin, Sukarmin; Nurachmah, Elly; Gayatri, Dewi (Universitas Aisyah Pringsewu, 2023)
Hypertension is a chronic disease with a prevalence that is still quite high in the world. Spirituality becomes an important element in increasing confidence in the success of hypertension therapy. This study aims to explore the spiritual experience of hypertensive patients conducting the therapy program. This study is a phenomenological qualitative research involving 6 participants of hypertensive patients at Aisyiyah Hospital of Kudus who met the criteria. The results of the study found 6 (six) themes, namely: 1) Belief in improving body condition and mildening of disease symptoms through worship, (2) Belief in worship as a means of self-improvement from bad habits and increasing goodness, (3) Belief in pain is understood as a means for self-introspection and improvement of worship, (4) Belief in synchronizing worship and effort as a means of healing, (5) Belief in doing relaxation therapy through worship, (6) Belief in disease symptoms hinders worship. These results show that spirituality plays an important role for hypertensive patients to increase the success of therapy.